2010
DOI: 10.1682/jrrd.2009.08.0108
|View full text |Cite
|
Sign up to set email alerts
|

Validation of erythropoietin use data on Medicare's End-Stage Renal Disease Medical Evidence Report

Abstract: Abstract-Data from Medicare's End-Stage Renal DiseaseMedical Evidence Report (Form 2728) suggest that underuse of erythropoiesis-stimulating agents (ESAs) may be contributing to anemia in predialysis patients. However, the data quality of Form 2728 is not known. ESA prescription records were confirmed in Department of Veterans Affairs (VA) data sets and/or ESA claims in Medicare files and compared with data collected on Form 2728 among 8,033 veterans who initiated dialysis in 2000 and 2001 and were eligible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In contrast to comorbidity data on Form CMS-2728, which has been validated with clinical data, 7 the validity of the Form CMS-2728 predialysis care measures has yet to be examined with the exception of one study investigating the validity of the predialysis ESA indicator in a Veterans Affairs population. 8 The accuracy of the predialysis ESA care indicator is especially important to scientific researchers, health care providers, and policy-makers in framing anemia management guidelines given recent findings suggesting that targeting higher hemoglobin levels with ESAs may confer no benefit or actually increase the risk of harm to CKD patients with anemia. [9][10][11][12][13] The purpose of this study was to compare predialysis ESA care reported on Form CMS-2728 with Medicare claims for ESA treatment submitted for patients 67 years and older at initiation of dialysis with Medicare as the primary payer.…”
Section: According To the Center For Medicaid And Medicare Services (Cmmentioning
confidence: 99%
“…In contrast to comorbidity data on Form CMS-2728, which has been validated with clinical data, 7 the validity of the Form CMS-2728 predialysis care measures has yet to be examined with the exception of one study investigating the validity of the predialysis ESA indicator in a Veterans Affairs population. 8 The accuracy of the predialysis ESA care indicator is especially important to scientific researchers, health care providers, and policy-makers in framing anemia management guidelines given recent findings suggesting that targeting higher hemoglobin levels with ESAs may confer no benefit or actually increase the risk of harm to CKD patients with anemia. [9][10][11][12][13] The purpose of this study was to compare predialysis ESA care reported on Form CMS-2728 with Medicare claims for ESA treatment submitted for patients 67 years and older at initiation of dialysis with Medicare as the primary payer.…”
Section: According To the Center For Medicaid And Medicare Services (Cmmentioning
confidence: 99%
“…Promoting high-quality care and providing the tools for independent living to veterans with spinal cord injury (SCI) [19], polytrauma [20], PTSD, substance-use disorder and other mental health conditions [21][22][23] and to others needing rehabilitative and assistive services [24][25] are high VA priorities. Investigating obesity and chronic kidney disease and its antecedents are important because these are among the most common chronic conditions afflicting veterans seeking care in the VA [26][27]. Understanding the healthcare needs and ensuring accessible care for women and other vulnerable populations [23,[28][29][30] are among the VA's top research priorities.…”
Section: Vital Veterans Research and Va Health Information Systemsmentioning
confidence: 99%
“…Data originating outside the VA are critical for learning about care received and costs of care for veterans obtaining services in the private sector and help to fill a gap in information for many studies. In addition to the National Patient Care Database [19][20][21]24,30], data sources evaluated include the Veterans Health Administration Corporate Data Warehouse [26], the VA's National Spinal Cord Dysfunction Registry [19], the Minimum Data Set (long-term care resident assessment) [24] [27], Medicaid and Medicare claims [29][30], and the Medicare Current Beneficiary Survey [31].…”
Section: Vital Veterans Research and Va Health Information Systemsmentioning
confidence: 99%
See 2 more Smart Citations